Forgiveness According to the Christian View in the Indonesian Context - Arina, Hein; Suoth, Vanny Nancy (Technium Social Sciences Journal, 2022)
Horizontal conflicts are triggered by intolerant attitudes. Intolerance arises when religious fanaticism is too excessive and there is no forgiveness. This research aims to describe forgiveness from a Christian point of view. To achieve this goal, the research was carried out with a qualitative approach using library research methods. The results show that for Christians, (i) forgiveness is the main condition for obtaining God’s grace, (ii) forgiveness is God’s commandment for His people to forgive fellow human beings, as God’s model provides forgiveness to sinful humans by sacrificing Jesus Christ, (iii) forgiveness is the need of people who believe in God, because without forgiving others, including their enemies, we will not get blessings from God, and (iv) forgiveness is the main condition for following Jesus and being forgiven. Forgiveness is the social capital of Christians to care for pluralism, the Unitary State of the Republic of Indonesia, and the Unity of Indonesia. With forgiveness, any conflicts that arise in the midst of society, the country, or even the world can be resolved. Both horizontal and vertical conflicts can be resolved. Forgiveness is the social capital of Christians to care for pluralism, the Unitary State of the Republic of Indonesia, and the Unity of Indonesia. With forgiveness, any conflicts that arise in the midst of society and the country, and even the world, both horizontal and vertical conflicts can be resolved